Investigating population‐scale allelic differential expression in wild populations of Oithona similis (Cyclopoida, Claus, 1866). Issue 16 (4th August 2020) - Laso‐Jadart, Romuald; Sugier, Kevin; Petit, Emmanuelle; Labadie, Karine; Peterlongo, Pierre; Ambroise, Christophe; Wincker, Patrick; Jamet, Jean‐Louis; Madoui, Mohammed‐Amin
Abstract: Acclimation allowed by variation in gene or allele expression in natural populations is increasingly understood as a decisive mechanism, as much as adaptation, for species evolution. However, for small eukaryotic organisms, as species from zooplankton, classical methods face numerous challenges. Here, we propose the concept of allelic differential expression at the population‐scale (psADE) to investigate the variation in allele expression in natural populations. We developed a novel approach to detect psADE based on metagenomic and metatranscriptomic data from environmental samples. This approach was applied on the widespread marine copepod, Oithona similis, by combining samples collected during the Tara Oceans expedition (2009–2013) and de novo transcriptome assemblies. Among a total of 25, 768 single nucleotide variants (SNVs) of O .  similis, 572 (2.2%) were affected by psADE in at least one population (FDR < 0.05). The distribution of SNVs under psADE in different populations is significantly shaped by population genomic differentiation (Pearson r  = 0.87, p  = 5.6 × 10 −30 ), supporting a partial genetic control of psADE. Moreover, a significant amount of SNVs (0.6%) were under both selection and psADE ( p  < .05), supporting the hypothesis that natural selection and psADE tends to impact common loci. Population‐scale allelic differential expression offers new insights into the gene regulation control in populations and its link with natural selection. Abstract : This research focused on analysing variation in allelic expression at population level, called here psADE. We extracted polymorphic data belonging to Oithona similis, a copepod, using metagenomic and metatranscriptomic data collected during the Tara Oceans expeditions. We found a link between loci targeted by psADE, population differentiation and selection and provided a functional analysis of these loci.